2021
DOI: 10.3390/ijerph18105431
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Injury and Illness in the Final 4 Weeks before a Trail Running Competition

Abstract: We aimed to (i) determine self-reported injury and illness frequency in trail runners 4 weeks preceding competition; (ii) compare athletes with and without injury/illness by sex, age, body mass index (BMI) and competition distance; (iii) describe mechanism of injury, anatomical region (injury)/organ system (illness) involved, consequences of injury on preparation and self-perception of injury severity; (iv) compare anatomical region (injury) and organ system (illness) by sex. A total of 654 trail runners (age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…La rodilla fue uno de los lugares con mayor prevalencia para ambas modalidades. Para corredores de trail running, la rodilla ha sido la región más reportada entre las lesiones musculo-esqueléticas, en estudios como el de Hsu et al (2020) con un 38%; Gajardo et al (2021), con 34,9% en hombres y un 30% en mujeres; para Viljoen et al (2021aViljoen et al ( , 2021b con un 29,8% y un 26,5%, respectivamente. Datos coincidentes con estudios similares, que también se concluye que uno de los sitios más comunes de lesiones fue la rodilla (Van Gent et al, 2007;Viljoen et al, 2021c).…”
Section: Prevalencia De Lesiones Según Región Anatómicaunclassified
See 2 more Smart Citations
“…La rodilla fue uno de los lugares con mayor prevalencia para ambas modalidades. Para corredores de trail running, la rodilla ha sido la región más reportada entre las lesiones musculo-esqueléticas, en estudios como el de Hsu et al (2020) con un 38%; Gajardo et al (2021), con 34,9% en hombres y un 30% en mujeres; para Viljoen et al (2021aViljoen et al ( , 2021b con un 29,8% y un 26,5%, respectivamente. Datos coincidentes con estudios similares, que también se concluye que uno de los sitios más comunes de lesiones fue la rodilla (Van Gent et al, 2007;Viljoen et al, 2021c).…”
Section: Prevalencia De Lesiones Según Región Anatómicaunclassified
“…Las lesiones en parte inferior de la pierna ha de ser considerada en corredores de trail running, en donde se observa que la prevalencia varía de 8,6% (Krabak et al, 2011), hasta el 32% (Hsu et al, 2020). Por otro lado, el pie también ha sido un lugar común de lesión para corredores de trail running con valores similares, entre el 11% y 16% como indican Gajardo et al (2021), González et al (2021, Hespanhol et al (2017), Hsu, et al (2020) o Viljoen, et al (2021b. Los datos mostrados anteriormente sobre corredores de trail running, concuerdan con los reportados por corredores de cross-country y orientación, pues en cuanto a la región anatómica, los lugares de lesión más prevalentes en estas modalidades fueron la parte inferior de la pierna, rodilla, tobillo y pie.…”
Section: Prevalencia De Lesiones Según Región Anatómicaunclassified
See 1 more Smart Citation
“…The knee and ankle are the most common sites for overuse injury. 6 Cross-sectional data collected over four trail races revealed that of the total respondent pool, 22% had suffered ITB syndrome, 10% had Achilles tendon injury, 9% had hamstring injuries, and 7% had calf muscle injury over the last 12 months, with an additional 19% reporting chronic injuries to the knee and lower leg. 3 Among the 2019 SkyRace competitor pool, muscle/tendon accounted for 44.1% of tissue type injuries.…”
Section: Chronic/ Overuse Injuriesmentioning
confidence: 99%
“…Exercise benefits have been well described in past literature ( Spittler & Oberle, 2019 ) with agreement that exercise contributes favorably to the physiological, psychological, and social development of the human being ( Bostancı et al, 2019 ). Traditional recreational running is a very popular form of exercise around the world ( Waśkiewicz et al, 2019 ) creating positive lifestyles changes ( Gajardo-Burgos et al, 2021 ). Over recent years, there has been increasing interest in running longer distances ( Spittler & Oberle, 2019 ), probably due to modern societal demands to overcome adversities and challenges ( Goddard et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%